Isolation, identification and optimization studies for l-asparaginase production from fungal isolates of marine sediments (Funded Work) - RASHMI HOSAMANI,; KALIWAL B B,; SHREERANGEGOWDA THIPPESWAMY, (International Journal of Pharma and Bio Sciences, 2017)
Marine microflora are a potential source of anticancer compounds and are the least explored, an attempt has been made to isolate the fungi from marine sediments of different coasts and screened for potential L-asparaginase production. Since malignant cells are dependent on L-asparagine for its survival. Out of eighteen isolates from five different coasts, three of isolates have exhibited significant L-asparaginase production on modified Czapek-Dox medium incorporated with 1% L-asparaginase and 0.009% phenol red indicator. Initial screening for CD21 & MD22 for asparaginase activity showed an activity of 0.14 and 0.07 IU/ml, respectively and were considered potential L-asparaginase producers. The molecular identification revealed that CD21 showed 99% similarity to Cladosporium tenuissimum and MD22 shows 94% similarity to Ramichloridium apiculatum. Optimization studies were carried out under submerged fermentation conditions. Cladosporium tenuissimum has shown maximum L-asparaginase production at 28°C, 1.5% glucose and 2% NaCl concentration. Similarly, Ramichloridium apiculatum exhibited the maximum activity at 28°C, 2% glucose and 2% NaCl concentration. The present study revealed that the two marine fungi are capable of producing bioactive enzyme L-asparaginase and can be further purified and characterized. This is the first report on L-asparaginase production by Cladosporium tenuissimum and Ramichloridium apiculatum.